2008
DOI: 10.1103/physreva.78.063417
|View full text |Cite
|
Sign up to set email alerts
|

Laser-pulse photoassociation in a thermal gas of atoms

Abstract: A nonperturbative treatment is presented for laser-pulse-driven formation of heteronuclear diatomic molecules in a thermal gas of atoms. Based on the assumption of full controllability, the maximum possible photoassociation yield is obtained. A one-dimensional model is used for calculating the photoassociation probability as a function of the laser parameters as well as for different temperatures. The dependence of the photoassociation yield on the laser frequency and amplitude reveals complex patterns of one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…3,12 The Morse oscillator parameters are D e = 0.1994a.u., r e = 1.821a.u., α = 1.189a.u. and M = 1728a.u., while the parameters of the permanent dipole function are q = 1.6a.u.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,12 The Morse oscillator parameters are D e = 0.1994a.u., r e = 1.821a.u., α = 1.189a.u. and M = 1728a.u., while the parameters of the permanent dipole function are q = 1.6a.u.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, if the colliding atoms are from two different species such that there exist a non-negligible permanent dipole coupling between the free atomic states and the rovibrational levels of the molecule ground state, an alternative photoassociation mechanism can be envisioned based on infrared laser pulses. 3 In this mechanism, the infrared laser can drive a transition from the free atomic state directly to the electronic bound state of the molecule to be formed.…”
mentioning
confidence: 99%
“…Our numerical control simulations for vibrational state-to-state transitions and for ultrafast electron tunneling have demonstrated that the new algorithm not only can greatly improve the search efficiency over its original one, but it also can attain good monotonic convergence quality in the case of the frequency constraints. The new algorithm is especially effective when the underling control dynamics involves a large number of energy levels or ultrashort control pulses, and it should be of particular interest for controlling complicated quantum processes including, for example, photoassociation reactions [1,2,26], molecular isomerization [27,28], and highorder harmonic generation [29][30][31], for which a judicious choice of sound initial control fields may be difficult.…”
mentioning
confidence: 99%
“…In recent years, much progress in the quantum control study has been made by drawing on powerful computers and state-of-the-art laser-pulse-shaping technologies [3], as well as optimal control theory [4][5][6][7][8]. Computationally, two key issues are usually encountered for solving optimal quantum control problems: (1) to find optimal control fields numerically and (2) to impose necessary frequency constraints on the calculated control fields. The former may require numerous iterations for solving the corresponding time-dependent Schrödinger equations, especially when starting with poorly chosen initial control fields (which often occurs when involving large numbers of energy levels or ultrashort control pulses), rendering it computationally formidable, whereas the latter usually requires frequency filtering at the end of each iteration, becoming detrimental to search effort.…”
mentioning
confidence: 99%
See 1 more Smart Citation